Incentive or penalty for researchers to make their publications freely accessible? The practice of Oslo University College. - Haugen, Trine B (Septentrio Conference Series, 2014)
As with other higher education institutions in Norway, Oslo University College (OUC) receives public funding for the published outlets based on the national documentation system. OUC has developed an internal system to stimulate the researchers to make their peer-reviewed scientific articles available in the institutional open digital archive (ODA). When an article is not transferred to ODA, the money allocated to the faculty based on this publication, is reduced by 50%.